NUCLEAR MATURATION RATE OF SHEEP OOCYTES IN VITRO: EFFECT OF STORAGE DURATION AND OVARY TEMPERATURE - Febretrisiana, A.; Setiadi, M. A.; Karja, N. W. K. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The present study was conducted to investigate the effects of duration and temperature storageof sheep ovaries on nuclear maturation in vitro of oocytes obtained from stored ovaries. Ovaries werecollected from slaughterhouse and stored in physiological saline for 2-4 h, 5-7 h and 8-10 h at varioustemperatures (27-28°, 36-37° and 4°C). Cumulus oocyte complexes (COCs) were collected with slicingmethod from each group and matured in vitro for 26 h. There was no difference between the proportionsof oocytes maturation to metaphase II when collected from ovaries stored at 27-28°C and 36-37°C for 2-7 h of slaughter. However, the percentages of oocytes from ovaries stored at 4°C were significantlylower (P<0.05) than those stored at higher temperature (69.23%, 70.83% and 45.65%, for 27-28, 36-37and 4°C at 2-4 h, respectively; 59.61%, 64,58% and 36.36% for 27-28, 36-37 and 4°C at 5-7 h,respectively). The proportion of oocytes meiosis to metaphase II (MII) were significantly (P<0.05)decreased when the ovaries stored at 27-28 and 36-37°C for 8-10 h, but not in oocytes stored at 4°C(24.37%, 7.84% and 45.23%, respectively). The maturation rate of oocytes from ovary stored at 4°C washigher than those collected from ovaries stored at higher temperature (P<0.05). This finding indicated that the storage of ovaries at 4°C for 8-10 h is effective for maintaining the development competence ofsheep oocyte better than storage at higher temperature.